Analisis Tingkat Kepuasan Pelanggan Terhadap Pelayanan Online Shop Kara Project - Wita Rohmatiana; Amin Sadiqin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
Customer satisfaction is the level of buyer sentiment after thinking between what is obtained and assumptions.  This inspection is intended to find out how big the level of customer satisfaction is given by Kara Project to its buyers. This study uses 5 components of service quality to determine the level of customer satisfaction depending on tangible evidence, reliability, responsiveness, assurance, and empathy. The motivation behind using these five measures or the servqual measure in estimating gaps.The procedure for collecting information uses a poll given to 80 respondents, after which validation and reliability tests are carried out using SPSS. This investigation obtained the average gap in each measurement: Tangible (- 4.78), Reliability (- 7.78), Responsive (- 12.78), Assurance (- 16.22), and Empathy (- 4.89). Therefore, it is stated that respondents really view the service quality of the Kara Project Business as something very negative.